Genetic Structure and Forensic Utility of 23 Autosomal STRs of the Ethnic Lao Groups From Laos and Thailand - Than, Khaing Zin; Muisuk, Kanha; Woravatin, Wipada; Suwannapoom, Chatmongkon; Srikummool, Metawee; Srithawong, Suparat; Lorphengsy, Sengvilay; Kutanan, Wibhu (Frontiers in Genetics, 2022)
The Lao Isan and Laotian are the major groups in the area of present-day northeastern Thailand and Laos, respectively. Several previous genetic and forensic studies indicated an admixed genetic structure of Lao Isan with the local Austroasiatic speaking groups, e.g. Khmer, whereas there is a paucity of reporting Laotian’s forensic short tandem repeats (STRs). Here, we newly generated 451 genotypes of seven Lao Isan and three Laotian populations (two Lao Lum and one Lao Thoeng) using 23 autosomal STRs embedded in VerifilerTM plus PCR Amplification kit. We reported allelic frequency and forensic parameters in different dataset: combined ethnic Lao groups, combined Lao Isan populations and combined Laotians. Overall, the forensic parameter results indicate that this set of STRs is suitable for forensic investigation. The anthropological results revealed the genetic homogeneity of Tai-Kadai speaking Lao groups from Thailand and Laos, consistent with previous studies, while the Austroasiatic speaking groups from southern Laos showed genetic relatedness to both Lao Isan and Khmer. In sum, STRs allelic frequency results can provide the genetic backgrounds of populations which is useful for anthropological research and also strengthens the regional forensic database in both countries.